Implementation of Digital Marketing in Increasing Sales of the Bronchips Brownies Chips MSME Brand - Robby Aditya; R. Yuniardi Rusdianto (CV. ITTC INDONESIA, 2024)
This research has the main objective, namely to find out and analyze strategies in the digital marketing dimension that are applied in increasing sales at Bronchips Brownie Chips MSMEs. The research carried out was descriptive qualitative research. This research was conducted on Bronchips Brownie Chips MSMEs. The subjects of this research are owners, employees and several consumers. Research Design & Methods: The data analysis method used in this research is SWOT analysis using the IFAS and EFAS tables. Findings: The results of research analysis using IFAS and EFAS show that Bronchips Brownie Chips have a strength factor that gets a total score of 3.01 while the weakness factor gets a total score of 0.34. Threats received a total score of 0.51 while Opportunities received a total score of 2.77. Overall, the total value of internal strategy factors is 3.35, while the total value of external strategy factors is 3.28. Judging from the consequences of the SWOT line, Bronchips Brownie Chips is in quadrant I with a value of (X;Y) (2.67; 2.26), namely by using aggressive planning. Making plans that require strengths to become opportunities is an aggressive strategy. Contribution & Value Added: The main contribution behind this research is for entrepreneurs and MSMEs who have not yet gone digital to know the potential and impact of implementing digital marketing